Institutional quality and the duration of agri-food trade flows - Helena Engemann; Yaghoob Jafari; Thomas Heckelei (Journal of Agricultural Economics, 2022)
Recent trade disruptions and their consequences on supply chains show the importance of stable trade relations for exporters' economic planning and importers' supply security. Both instability in trading partners' economic and institutional environment and differences between them are likely to exacerbate these disruptions. We investigate the role of exporters' institutional quality (IQ) and its similarity with importers' IQ in the stability of trade links. We focus on the trade links of agri-food products exported from sub-Saharan African (SSA) countries to the European Union (EU-28) and consider three dimensions of IQ: `government selection, monitoring, and replacement'; `efficiency of policy formulation and implementation'; and `respect of citizens and state for institutions'. Using a discrete-time duration model, we show that the duration of SSA exports to the EU-28 increases with higher exporters' IQ and similarity of trading partners' IQ. The strongest impact of exporters' IQ is associated with `government selection, monitoring, and replacement'. In terms of the similarity of trading partners, `respect of citizens and state for institutions' has the largest impact on trade durations. Our findings suggest that the improvement of countries' IQ may boost the stability of trade relationships. Moreover, the similarity of IQs between trading partners supports the stability of trade links and should be carefully considered when establishing new trade relations.
Keywords: 630; Agri-food trade; discrete-time model; institutional quality; trade duration